2019
DOI: 10.1051/parasite/2019014
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Parasitology: intestinal helminth parasites of the siganid fishSiganus rivulatusas bioindicators for trace metal pollution in the Red Sea

Abstract: Studies on host-parasite systems as bioindicators for monitoring trace metal pollution in marine environments are still scarce. Here, 11, 14 and 17 infrapopulations of Gyliauchen volubilis (Trematoda: Digenea), Procamallanus elatensis (Nematoda) and Sclerocollum rubrimaris (Acanthocephala), respectively, were collected from the fish Siganus rivulatus (Siganidae) in the Red Sea, from a chronically polluted small bay at Sharm El-Sheikh, South Sinai, Egypt. Water and sediment samples from the bay, tissue samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Heavy metals ingested by the fish (through intestines or their gills) are transported through the blood to the fish liver, where majority of the metals are extracted to manufacture organometallic complexes which are conveyed with bile to either the intestine, to continue the liver-intestinal cycles, or taken out of the fish body by egestion (Sures, 2001 and2003;Al-Hasawi, 2019;Mehana et al, 2020). Intestinal parasites do not have the capacity to manufacture their own cholesterols and fatty acids and, due to lipophilicity, they meddle in the cycle by easily ingesting the organo-metallic-bile complexes from their host, and this results to a reduction in the capacity of the fish host to accumulate metals (Al-Hasawi, 2019;Mehana et al, 2020). This could possibly suffice to define the higher concentrations of heavy metals in parasites in comparisons to the fish muscles in our study; and could also explain the reason Pb was not recorded from the muscle of Raimas nigeriensis but was found in the parasites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Heavy metals ingested by the fish (through intestines or their gills) are transported through the blood to the fish liver, where majority of the metals are extracted to manufacture organometallic complexes which are conveyed with bile to either the intestine, to continue the liver-intestinal cycles, or taken out of the fish body by egestion (Sures, 2001 and2003;Al-Hasawi, 2019;Mehana et al, 2020). Intestinal parasites do not have the capacity to manufacture their own cholesterols and fatty acids and, due to lipophilicity, they meddle in the cycle by easily ingesting the organo-metallic-bile complexes from their host, and this results to a reduction in the capacity of the fish host to accumulate metals (Al-Hasawi, 2019;Mehana et al, 2020). This could possibly suffice to define the higher concentrations of heavy metals in parasites in comparisons to the fish muscles in our study; and could also explain the reason Pb was not recorded from the muscle of Raimas nigeriensis but was found in the parasites.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of digestive tract in cestodes necessitates their ability to accumulate more heavy metals relative to their hosts; and utilize the bile salts in reproduction (Hassan et al, 2018). Similarly, Acanthocephalans and nematodes have wide range of capacity to extract bile than the intestine of their host fish (Sures et al, 2017;Al-Hasawi, 2019). Bamidele and Kuton (2016) reported that intestinal nematodes accumulated more metals (Cu, Cr, Ni, Pb and Fe) than their fish host muscle (Clarias gariepinus and Parachanna obscura) in Lekki lagoon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In all these studies, heavy metal concentrations were reported to be several thousand times higher in the parasites than in the fish hosts. Al-Hasawi [ 27 ] reported accumulation of lead and cadmium in Procamallanus elatensis (Nematoda) and Sclerocollum rubrimaris (Acanthocephala) from the fish Siganus rivulatus (Siganidae) collected in the Red Sea, Egypt, in concentrations higher than those of their fish hosts. Similarly, Elsayed et al [ 28 ] also reported significantly higher concentrations of heavy metals in trematodes infecting fish species in the Arabian Gulf in comparison with their fish hosts.…”
Section: Introductionmentioning
confidence: 99%